Adenovirus-mediated efficient gene transfer into cultured three-dimensional organoids. - Ning Wang; Hongyu Zhang; Bing-Qiang Zhang; Wei Liu; Zhonglin Zhang; Min Qiao; Hongmei Zhang; Fang Deng; Ningning Wu; Xian Chen; Sheng Wen; Junhui Zhang; et al. (PLoS ONE)
Three-dimensional organoids have been recently established from various tissue-specific progenitors (such as intestinal stem cells), induced pluripotent stem cells, or embryonic stem cells. These cultured self-sustaining stem cell-based organoids may become valuable systems to study the roles of tissue-specific stem cells in tissue genesis and disease development. It is thus conceivable that effective genetic manipulations in such organoids may allow us to reconstruct disease processes and/or develop novel therapeutics. Recombinant adenoviruses are one of the most commonly used viral vectors for in vitro and in vivo gene deliveries. In this study, we investigate if adenoviruses can be used to effectively deliver transgenes into the cultured "mini-gut" organoids derived from intestinal stem cells. Using adenoviral vectors that express fluorescent proteins, we demonstrate that adenoviruses can effectively deliver transgenes into the cultured 3-D "mini-gut" organoids. The transgene expression can last at least 10 days in the cultured organoids. As a proof-of-principle experiment, we demonstrate that adenovirus-mediated noggin expression effectively support the survival and self-renewal of mini-gut organoids, while adenovirus-mediated expression of BMP4 inhibits the self-sustainability and proliferation of the organoids. Thus, our results strongly suggest that adenovirus vectors can be explored as effective gene delivery vehicles to introduce genetic manipulations in 3-D organoids.